High HBA1C Level Is Associated With Low Heamoglobin Level - Rashid, Mafooza; Vinay Bharat, B. K. Gupta,; Gupta, Abhishek; Rashid, Zubair (International Journal of Innovative Research in Medical Science, 2018)
Background: The aim of the study was to compare the hemoglobin levels among normal controls (patients) and patients of TypeII diabetes with HbA1c levels below 7 % & above 7 %.and secondly to identify the undetected cases of anemia in TypeII diabetes. Materials & Methods - 50 patients of type 2 diabetes mellitus with their glycosylated hemoglobin levels less than 7 %, 50 patients of type 2 diabetes mellitus with their glycosylated hemoglobin levels more than 7 % attending the Medicine outpatient department of Subharti Medical College and Hospital will be the subjects for the study.50 age and sex matched controls will be selected randomly from Subharti Medical College and Hospital. Informed written consent will be taken from all the subjects. The study will be conducted from January 2016 to January. Result - We studied 50 cases with HbA1C>7(poor control),50 cases with HbA1C 5.6 to7 (good control) and 50 controls with HbA1C ≤5.6, we observed in cases with HbA1C>7 (poorly control) ,the mean HbA1C is 9.9±2 and mean Hb is 9.8±1.3 as compared to cases with HbA1C 5.6 to 7(good control) where mean HbA1C is 6±0.4 and Hb is 13±0.5,this clearly indicates that in cases HbA1C is more Hb levels are low and when HbA1C is less Hb levels are higher. Conclusion - In the present study we found negative correlation between HbA1c & Hb levels. As the value of HbA1c increases, as in cases of HbA1c >7(poor diabetic control), we found low Hb levels as compared to the cases with HbA1c <7(5.6-7) (good control).